Guidelines for Investing PRG, PRG-HIPC, and CCR Trusts Assets. (Policy Papers; Policy Paper ;, 2017)
On March 22, 2017, the Executive Board adopted the Guidelines for Investing PRG, PRG-HIPC, and CCR Trust Assets (the 'Guidelines') to establish the investment objectives and policies to guide the investment of assets of the PRG, PRG-HIPC, and CCR Trusts (the'Trusts') which are available for investment under the Trusts' instruments. These Guidelines are included in this document.